Xenopus Hybrids Provide Insight Into Cell and Organism Size Control - Gibeaux, Romain (Front Physiol, 2018)
Determining how size is controlled is a fundamental question in biology that is poorly understood at the organismal, cellular, and subcellular levels. The Xenopus species, X. laevis and X. tropicalis differ in size at all three of these levels. Despite these differences, fertilization of X. laevis eggs with X. tropicalis sperm gives rise to viable hybrid animals that are intermediate in size. We observed that although hybrid and X. laevis embryogenesis initiates from the same sized zygote and proceeds synchronously through development, hybrid animals were smaller by the tailbud stage, and a change in the ratio of nuclear size to cell size was observed shortly after zygotic genome activation (ZGA), suggesting that differential gene expression contributes to size differences. Transcriptome analysis at the onset of ZGA identified twelve transcription factors paternally expressed in hybrids. A screen of these X. tropicalis factors by expression in X. laevis embryos revealed that Hes7 and Ventx2 significantly reduced X. laevis body length size by the tailbud stage, although nuclear to cell size scaling relationships were not affected as in the hybrid. Together, these results suggest that transcriptional regulation contributes to biological size control in Xenopus.